Polydioxanone and Botulinum Toxin threads as an alternative in the treatment of Facial Bell's Palsy: experience report (Research, Society and Development, 2021)
Bell's Palsy affects the seventh cranial nerve which unilaterally causes loss of function of the facial muscles. This study aims to report the experience of an alternative treatment for Bell's palsy. This is an experience report that describes the follow-up of a patient with Bell syndrome, experienced in a private clinic in the state of Tocantins. During the period between October 2020 and September 2021, 13 sessions were performed with the patient using botulinum toxin and polydioxanone threads, where an improvement in muscle motility and a reduction in asymmetry can be seen. The diagnosis is clinical and also exclusionary, where a detailed physical examination must be performed, the treatment involves the use of medication, physical methods and even surgery. The alternative treatment used in the reported case proved to be quite effective, improving the patient's facial esthetics and self-esteem.